The local-overall flexural interaction of fixed-ended plain channel columns and the influence on behaviour of local conditions at the constituent plate ends - Loughlan, Joseph; Yidris, Noorfaizal (Elsevier, 2014)
This paper examines the effect of the local support conditions at the ends of the constituent plates of plain channel section columns when subjected to uniformly compressed loading. The buckling and post-buckling interactive response of the columns have been determined through the development of suitable finite element modelling strategies and solution procedures which take due account of the influence of material nonlinearity and geometrical imperfections. Uniformly compressed loading means, of course, fixed conditions at the column ends with respect to global rotations and the ends of the constituent plates of the cross-section can be treated as either locally rotationally constrained or locally rotationally free. These two conditions are shown to lead to quite different characteristic interactive responses of the columns due to amplitude modulation in the buckling mode for the rotationally constrained case.